Socio-cultural and Economic Status of Gurung women: A study of Birendranagar Municipality, Ward no. 1, Surkhet - Dhakal, Aishwarya Prashad (Prajnik Bimarsha प्राज्ञिक विमर्श, 2024)
Women and ethnicity are extremely important to Nepal's overall growth. Women and ethnicity play important roles in enhancing a nation's reputation abroad. The development of Nepal's economy is largely driven by women. It significantly influences Nepalese society and the economy. Women are revered as historical figures in the country. This study is conducted at Gurung community of Birendranagar Municipality Ward No. 1 Surkhet. The main objective of this study is to find out social, cultural and economic conditions and examining the changing pattern of social, cultural and economic situation of Gurung community. This research carried out a theoretical proportion of Gurung women in the situation of contemporary society of Nepal. This study had carried out to discover the demographic socio-cultural and economic profile and to suggest some remedial measures for their better economy. This study was conducted in a descriptive research design with purposive sampling. The information was gathered using both types of quantitative and qualitative data through households' survey, interview observation and questionnaires as tools together and generalization of the study. This study has also aimed to discover the major characteristics of Gurung women in contemporary society. Even though they have need to more empowerment providing by education, loan for business, and awareness program.